Evaluation of reparative capabilities in a chronic wound defect in patients with complicated forms of varicose veins - S.I. Savoliuk; A.R. Dembitskyi (Медицина неотложных состояний)
Background. The purpose was to determine the effectiveness and results of clinical application of endovenous laser ablation and endovenous electric welding with local treatment of trophic ulcer of venous origin using platelet rich plasma (PRP); to determine the difference in the expression of CD68 marker when treating C6 chronic vein disease of the lower extremities with PRP compared to traditional methods. Materials and methods. Treatment outcomes were analyzed in 54 patients with C6 chronic vein disease of the lower extremities. The mean age in the main and comparison groups was 63.4 and 62.8 years, respectively. Main group: 28 patients, 11 males (39.3 %) and 17 females (60.7 %), who underwent preoperative preparation and subsequent treatment with PRP and minimally invasive surgery. Comparison group: 26 patients, 5 men (19.2 %) and 21 women (80.8 %), who received standard local treatment and underwent surgical intervention, including crossectomy, stripping, mini-phlebectomy, sclerotherapy. Results. The level of pain decreased by more than 50 % on day 4 of treatment in 92.9 % of patients in the main group and 38.5 % in the comparison group. After 2 years, fibrosis of the target veins was achieved in 100 % of cases. The proposed algorithm of preoperative preparation resulted in trophic ulcer clearing on day 16.0 ± 4.3 and healing on day 31.0 ± 5.2 in 95 % of patients in the main group, while in the comparison group, trophic ulcer clearing was observed on day 23.0 ± 6.8 and healing on day 44.0 ± 4.7 in 95 % of cases. The expression of CD68 marker in 75 % of patients in the main group was estimated at 3 points, while in the comparison group, this level of expression was noted in 10 % of patients indicating creation of favorable conditions for faster healing of the ulcerative defect and stimulation of neoangiogenesis in the main group. Conclusions. The use of the immunohistochemical method to objectify neoangiogenesis with the use of PRP in the treatment of trophic skin defects has made it possible to confirm its effectiveness and necessity for this category of patients.